Type 2 diabetes mellitus and dyslipidaemia: effects of genetic variation in African populations - Tanyanyiwa, Donald Moshen (Department of Pathology, 2019)
Background: Low-density lipoproteins (LDL) have been associated with damage to the cardiovascular system in patients with type 2 diabetes mellitus (T2DM). These patients are two (2X) to four (4X) times more likely to develop cardiovascular diseases (CVD) compared to non-diabetic patients due to dysfunctional lipoprotein metabolism. Normal lipid metabolism involves interconversion and transfer of molecules regulated by several enzymes such as Apolipoprotein E (ApoE) and proprotein convertase subtilisin/kexin type 9 (PCSK9). ApoE and PCSK9 are involved in clearance of lipoproteins and therefore, influence lipid profiles. Association between ApoE and T2DM in cardiovascular diseases have been widely reported. PCSK9 on the other hand is emerging as an important player in lipid metabolism but its effects in diabetes are not known. Studies on both ApoE and PCSK9 in African populations are in its infancy. Each year, CVD kills more people than any other cause of death. Many CVDs can be traced back to pathological process of atherosclerosis, in which fatty material collects along walls of arteries, limiting flexibility and obstructing blood flow. T2DM alone has been classified as a major factor for development of CVD and one of its complications is the development of dyslipidaemia. Unlike PCSK9, genetic polymorphisms in ApoE have been well characterised as important dyslipidaemia genetic markers associated with coronary artery disease. The association between ApoE and PCSK9 gene polymorphisms with dyslipidaemia in T2DM was evaluated. Diabetic dyslipidaemia presents as a triad of high triglycerides, high LDL and low high-density lipoprotein (HDL). Aims and Objectives: This study aimed to evaluate the role of genetic variation in genes coding for ApoE2 and PCSK9 on dyslipidaemia in South African diabetic patients. Main objectives’ included recruitment of participants, genetic characterisation of ApoE and PCSK9 and determination of the lipid profiles for the recruited participants. Methods: Two hundred and forty-four (n=244) participants were recruited from the Baragwaneth diabetic clinic, using a retrospective approach. The participants comprised of two groups, (i) dyslipidaemic, and (ii) non-dyslipidaemic (controls). The dyslipidaemic group was further divided into three groups; i) those with high cholesterol only, ii) those with high triglycerides only and iii) those with both high cholesterol and triglycerides which is referred to as the mixed group. Clinical and demographic parameters were retrieved from hospital records with the consent of the participants. Ethical clearance was obtained from the University of Cape Town and University of Witwatersrand. Genetic characterisation of ApoE was carried out using polymerase chain reaction (PCR) coupled to restriction fragment length polymorphism (RFLP) and confirmed through sequencing while characterisation for PCSK9 was carried out through Sanger sequencing. Results: Of the 244 participants, 165 were dyslipidaemic while 79 were not dyslipidaemic. The 165 dyslipidaemic participants were further divided into 33.3% (n=55) those with high cholesterol, 29.1% (n=48) those with high triglycerides and 37.6% and (n= 62) those with high cholesterol and triglycerides (mixed). The cohort comprised of 128 (52%) females, median (IQR) age 56.0 (48.0 – 64.0) years and 116 (48%) males with median (IQR) age of 56.5 (48.0 – 63.0) years. Most of the characteristics between the dyslipidaemic and nondyslipidaemic participants were significantly different as expected in a purposive sampling technique. ApoE3/4 genotype had the highest frequency distribution (41%) while ApoE2/3 genotype had the lowest frequency (7%). An uncharacterised ApoE referred to in the study as ApoE X with a frequency distribution of 6%, was reported for the first time. The selected measured parameters evaluated against a set of variables showed a significant association between HbA1c and age (p=<0.008) is reported. TC (p=0.00092), LDL (p=0.0184) and TG (p=0.0175) were strongly associated with poor glycaemic. Both LDL (p=0.0174 and HDL (p=0.0072) were associated with age. Homozygous ApoE2/2 and heterozygous ApoE2/3 genotypes correlated with poor glycaemic control with a median HbA1c of 10.95% (IQR 5.88-14.98%) and 10.20% (IQR 6.20-15.80%), respectively; while homozygous ApoE4/4 carriers displayed good glycaemic control with a median HbA1c of 6.60% (IQR 5.70 – 2.30%). Carriers of homozygous ApoE3/3 genotype had the highest median TC of 6.06mmol/L (IQR 5.48 -– 6.71mmol/L) while homozygous ApoE4/4 carriers had the highest median triglycerides of (2.94 (IQR 1.75 – 5.13 mmol/L). Carriers of homozygous PCSK9 rs505151 A/A (E670G) genotype had the highest frequency distribution in both groups of participants with dyslipidaemic (55.1%) and non-dyslipidaemic (63. 5%), followed by carriers of heterozygous PCSK9 rs505151G/A at 40.6% and lastly carriers of PCSK9 rs505151G/G at (9.5%). On the other hand, carriers of homozygous PCSK9 rs28362286 C/C genotype were predominantly distributed with a frequency of 94.2% and PCSK9rs28362286C/A had a very small frequency distribution of 5.8% while PCSK9rs28362286A/A was absent in this population. Carriers of PCSK9 rs505151A/A genotype had higher HbA1c with a median of 10.10% (IQR 7.48 – 12.90) compared to PCSK9 rs505151 G/A genotype with a median of 9.00% (IQR 7.03 –11.35). The results show that PCSK9 rs505151G/A with lower HbA1c had non-significantly higher TC, LDL, TG and non-HDL but lower HDL compared to PCSK9 rs505151A/A genotype. The results revealed no direct reciprocal relationship between glycaemic control and level or type of dyslipidaemia. Conclusions: The study showed the effects of ApoE and PCSK9 genetic variation on the dyslipidaemia seen in black South African diabetic participants. Therefore, this study through ApoE and PCSK9 genotypes show that the diabetic dyslipidaemia has an underlying genetic influence. In addition, to the well-characterised ApoE genotypes, an uncharacterised genotype referred to as ApoE X genotype is reported. With these findings, consideration to explore possible underlying genetic predisposition is recommended especially in diabetic patients with dyslipidaemia that responds poorly to standard therapy.